Microstructure Degradation of LSM/YSZ Cathodes for Solid Oxide Fuel Cells Aged in Stack after Long Operation Time. Issue 13 (1st January 2017) - Zekri, Atef; Schnetger, Bernhard; Essafi, Mohamed Amine; Plaggenborg, Thorsten; Parisi, Jürgen; Knipper, Martin
Abstract : The performance of solid oxide fuel cells (SOFCs) as well as their lifetime are strongly dependent on electrode microstructure. In this paper the effects of long exposure time (up to 20 000 h) under realistic operation conditions (T = 850°C, J = 190–250 mA·cm −2 ) in the microstructural degradation are investigated for porous Lanthanum Strontium Manganite (LSM)/Yttria-Stabilized Zirconia (YSZ) cathodes in order to understand the microstructural evolution in SOFC cermet cathodes. Data acquired from high resolution and optimized 3D imaging technique Focused Ion Beam (FIB)/Scanning Electron Microscope (SEM) was used in the quantification of various cathode structures aged during different operating times (2 500 h, 15 000 h and 20 000 h). The methodologies of tomography enable a precise quantification of particle grain growth, connectivity, tortuosity factor and triple phase boundary length (TPBL ). Statistically no significant 3D microstructural changes were observed in the cathode by increasing the operating time. The quantitative results from the FIB/SEM tomography were combined with additional semi quantitative measurements done by X-ray fluorescence (XRF) in order to study the chrome poisoning in the cathodes. Both techniques led to a more thorough description of the degradation phenomena in the microstructures of LSM-based cathodes.